2003
DOI: 10.4049/jimmunol.170.12.5861
|View full text |Cite
|
Sign up to set email alerts
|

Minor Histocompatibility Antigens on Canine Hemopoietic Progenitor Cells

Abstract: Adoptive immunotherapy with CTL against minor histocompatibility Ags (mHA) provides a promising way to treat leukemia relapse in allogeneic chimeras. Here we describe the in vitro generation of CTL against mHA in the dog. We tested their inhibitory effect on the growth of hemopoietic progenitor cells stimulated by hemopoietic growth factors in a 4-day suspension culture. CTL were produced by coculture of donor PBMC with bone marrow-derived dendritic cells (DCs). These DCs were characterized by morphology, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…Using this criterion, we demonstrate that LPS-stimulated MoDC in contrast to MΦ up-regulated MHC II, CD80 and CD40, similar to observations found with other species [3, 8, 33] upon stimulation with ligands to TLR2, -3 and -7 MoDC reacted with a significant up regulation of MHC II and CD86 as seen in other species [27, 34, 42]. The lack of responsiveness to TLR9 ligand CpG could be related to observations also found for humans and pigs, which describe that only plasmacytoid DC express this receptor [34, 40]. Future studies are required with more CpG sequences and the canine plasmacytoid DC need to be identified before any conclusion can be drawn.…”
Section: Discussionsupporting
confidence: 84%
“…Using this criterion, we demonstrate that LPS-stimulated MoDC in contrast to MΦ up-regulated MHC II, CD80 and CD40, similar to observations found with other species [3, 8, 33] upon stimulation with ligands to TLR2, -3 and -7 MoDC reacted with a significant up regulation of MHC II and CD86 as seen in other species [27, 34, 42]. The lack of responsiveness to TLR9 ligand CpG could be related to observations also found for humans and pigs, which describe that only plasmacytoid DC express this receptor [34, 40]. Future studies are required with more CpG sequences and the canine plasmacytoid DC need to be identified before any conclusion can be drawn.…”
Section: Discussionsupporting
confidence: 84%
“…15,16 GVHD can also target recipient hematopoietic stem cells. [17][18][19][20][21] However, none of the patients in this report had evidence of immune-mediated hemolysis despite the presence of ABO incompatibilities in 6 of the 8 patients. Moreover, none of the patients had evidence of GVHD, and it is therefore very unlikely that selective depletion of maturing recipient RBCs was caused by alloimmune responses directed against these cells.…”
Section: Discussionmentioning
confidence: 99%
“…In another experiment, the responsiveness of the cells to hematopoietic growth factors was tested. Cells harvested from day 6 of coculture proliferated in response to a mixture of hematopoietic growth factors known to support the growth of canine hematopoietic progenitor cells [12], whereas much less proliferation was observed with cells harvested from day 0 of coculture (data not shown). Importantly, our in vitro differentiation results were obtained using cells at passages 10 -12.…”
mentioning
confidence: 94%